2016
DOI: 10.1007/s00784-016-1767-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bone mineral density and bisphosphonate therapy on the determinants of oral health and changes on dental panoramic radiographs in postmenopausal women

Abstract: BP therapy could have a negative influence on the determinants of oral health in postmenopausal women with osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
0
18
0
2
Order By: Relevance
“…Some authors have shown that CAL was consistently related to BMD but presented no statistical significance (Reinhardt et al 1999; Tezal et al 2000; Pilgram et al 2002). Otherwise, other authors have found no association between CAL and BMD, osteopenia, and/or osteoporosis (Hildebolt et al 1997; Weyant et al 1999; Famili et al 2005; LaMonte et al 2013; Moeintaghavi et al 2013; Grgić et al 2017).…”
Section: Resultsmentioning
confidence: 91%
“…Some authors have shown that CAL was consistently related to BMD but presented no statistical significance (Reinhardt et al 1999; Tezal et al 2000; Pilgram et al 2002). Otherwise, other authors have found no association between CAL and BMD, osteopenia, and/or osteoporosis (Hildebolt et al 1997; Weyant et al 1999; Famili et al 2005; LaMonte et al 2013; Moeintaghavi et al 2013; Grgić et al 2017).…”
Section: Resultsmentioning
confidence: 91%
“…First, hormone therapy and osteoporosis medication data were not collected. Some studies have pointed out that estrogen use can prevent from tooth loss in PMW [5,14], while the widely used bisphosphonate drugs for the treatment of osteoporosis have been reported to have potential risks of osteonecrosis of the jaw [30]. According to other surveys, only about one-third of Taiwanese PMW have used or are currently treated with hormones or prescription drugs for osteoporosis [13,31].…”
Section: Discussionmentioning
confidence: 99%
“…Bone density changes throughout life, but after the menopause a decrease in estrogen production occurs, which seems to be associated with an increased risk of osteoporosis. Decreased bone density in the jaw bone in subjects with osteoporosis is obviously compatible with this condition, leading to attachment loss in individuals with PDIS [ 72 , 73 , 81 , 82 ]. Besides being associated with decreased bone density, estrogen deficiency also affects the other periodontal tissues and the immune response against the periodontal biofilm in a proinflammatory direction [ 81 ].…”
Section: Explanatory Modelsmentioning
confidence: 99%